Improving Employee Performance Through Good Organizational Culture and Work Motivation - Shalahuddin Shalahuddin (Advances in Human Resource Management Research, 2022)
This research was conducted at the Office of the Department of Transportation in Buukumba Regency. The aims of this study were (1) to analyze the effect of organizational culture on the performance of Transportation Service Employees in Bulukumba Regency, (2) to analyze the effect of motivation on the Performance of Transportation Service Employees in Bulukumba Regency. The population in this study were all employees of the Department of Transportation in Bulukumba Regency with a total sample of 58 people. Data collection methods used are interviews, documentation, and questionnaires. Methods of data analysis in this study using test instruments (validity test and reliability test), descriptive analysis, multiple regression analysis, hypothesis testing partial test (t) and simultaneous test (F) and the coefficient of determination. The conclusion of this research is that organizational culture and motivation have a significant effect on the performance of employees of the Department of Transportation in Bulukumba Regency. We suggest that the leaders of the Department of Transportation should always appreciate every achievement that has been achieved by their employees because the statement "The organization (leader) gives awards for innovations or achievements that you do at work" has a fairly low response, meaning employees need appreciation for the achievements that have been achieved. , because giving awards can improve good employee performance